The Influence of Social Capital and Marketing Capability on Marketing Performance Through Innovation as a Mediating Factor : Study Of Batik Tulis Kebon Indah MSMEs In Bayat Klaten - Wibowo, Sugeng; Farida, Naili; Dewi, Reni Shinta (University of Merdeka Malang, 2024)
This study explores the significance of Micro, Small, and Medium Enterprises (MSMEs), particularly within the batik industry, in Indonesia's economic landscape. The research focuses on the impact of social capital and marketing capability on marketing performance, with innovation serving as a mediating factor. The study concentrates on the Kebon Indah Batik Tulis MSMEs in Bayat, Klaten, employing the Resources Based View (RBV) theoretical framework. A quantitative methodological approach was implemented, utilizing questionnaires with a five-point Likert scale to gather data from 100 respondents. The data analysis was conducted using Structural Equation Modeling (SEM) through Smart-PLS version 4.1.0.4. Findings indicate that social capital and marketing capability exert positive and significant influences on both innovation and marketing performance. Moreover, innovation is demonstrated to mediate the relationship between social capital and marketing capability with marketing performance. These results offer valuable insights for MSME stakeholders in identifying crucial factors affecting marketing performance. Future research recommendations include employing qualitative methods to gain deeper insights into the variables and their interaction patterns. Additionally, investigating Batik Tulis MSMEs with diverse characteristics is suggested to enhance the generalizability of the findings.